Nanocomposites of Polymers and Inorganic Particles - Striccoli, Marinella; Comparelli, Roberto; Panniello, Annamaria (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The book covers all of the specific aspects of this topic, ranging from preparatory approaches, functionalization strategies of NPs and polymers, processing and integration of nanocomposites in additive manufacturing materials, and technological methodologies to obtain functional multiphase materials for advanced application.